Gender Justice: Construction of Family Guidance and Counseling by the Islamic Religious Extension Communication Forum - Aibak, Kutbuddin; Musonnif, Ahmad (Martabat: Jurnal Perempuan dan Anak, 2023)
This paper aims to look at the construction of gender equality in family guidance and counselling. The construction of gender equality in the family aims as a preventive measure against family problems. This is a pattern and strategy to respond to various family problems caused by gender inequality, such as domestic violence. Through this problem, the Islamic Religious Extension Communication Forum (FKPAI) has a gender equality-based family guidance and counselling curriculum. In order to see the pattern and construction of gender equality in family guidance and counselling by FKPAI, this paper uses a qualitative method through a case study presented through descriptive techniques and content analysis as a data analysis method. The findings in this paper show that the pattern of guidance and counselling of FKPAI of the Ministry of Religious Affairs of Tulungagung and Trenggalek Regency prioritises the approach aspect. The construction of gender equality in marriage guidance and counselling by FKPAI is based on the fact that gender equality has been able to become a preventive aspect of family problems.